Geliat Ekonomi Rumah Tangga Melalui Pemasaran Industri Rumah Tangga Di Media Sosial - Arief Adhy Kurniawan (Jurnal Pengabdian Mitra Masyarakat (JPMM), 2020)
Home industry can be done by focusing on superior household products. Every household has a superior product that can be used to improve the economy. The product can initially be marketed to the surrounding environment, then it is expected to expand its marketing more broadly. This is done by marketing through social media technology tools. The housewives of the PKK in Grendeng Kelurahan have mobile devices that can be used to access social media. The PKK executive organization in Grendeng village level already has a social media group that includes the whatsapp group. The group is used for communication between members in the group. However, they do not yet have a special group that is used for buying and selling forums. The reason for the importance of creating a buying and selling forum group is less ethical formal groups are used for promotional activities. The activity was carried out on Wednesday, August 7, 2019 at the Grendeng Village Hall. The activity was carried out with 39 participants. Activity Output in the form of a buying and selling forum on the Whatsapp group. The group has been used to sell household mainstay products in Grendeng. So with this buying and selling forum the public can offer their products and market more broadly.